1987
DOI: 10.1111/j.1471-4159.1987.tb05748.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Somatostatin‐Containing Fibers Projecting from the Pallidal Complex to the Striatum of the Rat

Abstract: The origin of afferent somatostatin-containing fibers terminating in medial and ventral parts of the striatum has been investigated by performing various neurochemical and surgical lesions in the rat. Lesions of the anterior hypothalamus, amygdala, and the hippocampal commissure as well as lesions with 6-hydroxydopamine and 5,7-dihydroxytryptamine failed to decrease striatal somatostatin levels. However, thermal coagulation of the globus pallidus or knife-cut lesions performed ventrally to the striatum resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Since these neurotoxins are known to elicit neuronal destruction sparing axons and nerve terminals, it was suggested that NPY immunoreactivity in the striatum is entirely derived from the population of interneurons. In contrast, striatal somatostatin immunoreactivity is related partly to striatal projection fibres of which the origin is still under discussion (Beal and Martin, 1983;Salin et al, submitted;Widmann et al, 1987). Several lines of evidence indicate that the nigrostriatal dopaminergic pathway influences striatal NPY metabolism.…”
Section: Fig 5 Schematic Diagram Illustrating the Topographical Chamentioning
confidence: 89%
“…Since these neurotoxins are known to elicit neuronal destruction sparing axons and nerve terminals, it was suggested that NPY immunoreactivity in the striatum is entirely derived from the population of interneurons. In contrast, striatal somatostatin immunoreactivity is related partly to striatal projection fibres of which the origin is still under discussion (Beal and Martin, 1983;Salin et al, submitted;Widmann et al, 1987). Several lines of evidence indicate that the nigrostriatal dopaminergic pathway influences striatal NPY metabolism.…”
Section: Fig 5 Schematic Diagram Illustrating the Topographical Chamentioning
confidence: 89%
“…The second place in which numerous perikarya were seen was just above the bed nucleus of the stria terminalis, near the globus pallidus. In the rat, the striatal afferent neurons that contain SOM may originate in the area of the globus pallidus [37]. The medium-sized, spiny interneurons that contain SOM/NPY contact the medium-sized spiny neurons through symmetrical synapses and non-synaptic junctions [38].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies in mammals have revealed that somatostatin is produced in several tissues and play important roles in coordinating growth, development and metabolism [8][9][10] . Somatostatin is widely expressed in the CNS where it is mainly found in the hypothalamus [11][12][13] , amygdala 14,15 , preoptic area 16 , hippocampus [17][18][19] , striatum 20 , deeper layers of the cerebral cortex [21][22][23] , brainstem 24,25 and the spinal cord [26][27][28][29] . Somatostatin has been shown to act as a neuromodulator involved in sleep 30 , learning 31,32 , food intake 33 , reproduction 34 , neuropathology 35 and locomotor activity 36,37 .…”
mentioning
confidence: 99%